Chronological dimensions and Cultural Layers of Tamils - D. Muthukrishnan (Journal of International Islamic Law, Human Right and Public Policy, 2025)
This research scrutinises the chronological stratification and cultural layers of Tamil society, situating its evolution within a long-term historical framework. Drawing upon interdisciplinary sources—including archaeological findings, literary corpora, and epigraphical records—the research delineates the temporal trajectory of Tamil civilization, mapping transformations in socio-political structures, religious practices, linguistic developments, and material culture. The analysis foregrounds the dynamic interplay between continuity and change, elucidating the successive historical phases have cumulatively shaped the complex, multi-layered identity of the Tamil people. By integrating temporal and cultural dimensions, the study provides a nuanced understanding of Tamil heritage as a historically resilient and adaptive civilizational formation.